Determination and ecological risk assessment of phthalic acid esters in marine sediments - HU Hongmei; LI Tiejun; ZHANG Lu; HAO Qing; SUN Xiumei; JIN Yanjian; YING Zhongzhen; GUO Yuanming (浙江大学学报. 农业与生命科学版)
We proposed a new method for the determination of 16 phthalic acid esters (PAEs) in marine sediments using gas chromatography-mass spectrometry (GC-MS) combined with ultrasonic extraction and dispersive solid phase extraction cleanup. Moreover, the contents of PAEs in marine sediments of Sanmen Bay, Taizhou and waters of Nanji Island, Wenzhou were detected and their ecological risk was assessed. Under the optimized condition, the linearity of this method ranged from 1 to 1 000 μg/L, with regression coefficients ranging between 0.999 1 and 0.999 9. The limits of detection were in the rang of 0.10-0.25 μg/kg. The recoveries of spiked 16 PAEs at different concentration levels were in the range of 75%-116%, with relative standard deviations of 3.1%-7.2%. The results showed that the total concentration of phthalate esters ranged from 297.43 to 550.25 μg/ kg. Diisobutyl phthalate (DIBP), di-n-butyl phthalate (DBP) and di (2-ethylhexyl) phthalate (DEHP) were the predominant compounds in all detected seafood, accounted for 88.7%-96.7% of the total PAEs. Marine sediment’s ecological risk was assessed with the methods of sediment quality guidline and risk quotient. The sediment quality guidline results showed the contents of PAEs in the sediments were all lower than the environmental risk limits, which indicated low ecological risk. The risk quotient values of PAEs were in the following order: DBP>DIBP>DEHP, and DBP was high risk to algae and medium risk to crustaceans and fish, and DIBP was medium risk to crustaceans, and DEHP was low risk to aquatic organisms. Overall, the risk of PAEs on algae was the largest, followed by crustaceans, minimal risk for fish, and the health risk of Sanmen Bay, Taizhou was slightly higher than that of waters of Nanji Island, Wenzhou.